Protocol for the isolation and characterization of murine hematopoietic stem and progenitor cell-derived extracellular vesicles - Federica Zanotti; Ilaria Zanolla; Massimo Bonora; Claudia Morganti; Barbara Zavan; Letizia Ferroni; Paolo Pinton; Keisuke Ito (STAR Protocols)
Summary: Hematopoietic stem cells (HSCs) maintain their self-renewal capacity in an autocrine manner through hematopoietic stem and progenitor cell (HSPC)-derived extracellular vesicles (EVs). Here, we present a protocol for the isolation and characterization of EVs from HSPCs starting from an in vivo murine model. We describe steps for murine bone marrow isolation, HSPC staining and sorting, HSPC-derived EV isolation, size and concentration characterization, and EV visualization and marker description.For complete details on the use and execution of this protocol, please refer to Bonora et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.